Human rights from exclusion to inclusion : principles and practice. An anthology from the work of Theo van Boven - Coomans, Fons (The Hague : Kluwer Law International, 2000)
BMLIK
Engels
Monografie
Keywords: mensenrechten; sociale uitsluiting